Origami activities are effective in improving fine motor skills of stunted children - Khasanah, Uswatun; Almadevy M.J, Anindhita; Pratamawati, Tiar M; Suhaeni, Eni; Sulistiyana, Catur Setiya; Wahidin, Dea Triasari Indriyanti (BKM Public Health and Community Medicine, 2025)
Purpose: This study aimed to evaluate the effectiveness of origami activities on fine motor development in stunted children aged 3–5 years. Methods: A quasi-experimental study with a pretest–posttest control group design was conducted at the Babakan Community Health Center, Cirebon District. A total of 60 stunted children were recruited and equally assigned to intervention and control groups (n = 30 each group). The intervention group participated in three origami activity sessions, while the control group did not receive the intervention. Fine motor skills were assessed before and after the intervention using the KPSP questionnaire. Group differences were analyzed using the Mann–Whitney test. Results: Children in the intervention group showed significantly greater improvement in fine motor skills compared with the control group (p = 0.014). Conclusion: Origami activities are effective in enhancing fine motor development among stunted children and may serve as a simple, low-cost intervention in community health settings.